Internationalization and the evolution of corporate valuation - Levine, Ross, 1960- 16.04.1960- (NBER working paper series, 2005)
"By documenting the evolution of Tobin's "q" before, during, and after firms internationalize, this paper provides evidence on the bonding, segmentation, and market timing theories of internationalization. Using new data on 9,096 firms across 74 countries over the period 1989-2000, we find that Tobin's "q" does not rise after internationalization, even relative to firms that do not internationalize. Instead, "q" rises significantly one year before internationalization and during the internationalization year. But, then "q" falls sharply in the year after internationalization, relinquishing the increases of the previous two years. To account for these dynamics, we show that market capitalization rises one year before internationalization and remains high, while corporate assets increase during internationalization. The evidence supports models stressing that internationalization facilitates corporate expansion, but challenges models stressing that internationalization produces an enduring effect on "q" by bonding firms to a better corporate governance system"--National Bureau of Economic Research web site